Higher dietary fibre intake is associated with increased skeletal muscle mass and strength in adults aged 40 years and older. Issue 6 (29th September 2021) - Frampton, James; Murphy, Kevin G.; Frost, Gary; Chambers, Edward S.
Abstract: Background: Skeletal muscle mass begins to decline from 40 years of age. Limited data suggest that dietary fibre may modify lean body mass (BM), of which skeletal muscle is the largest and most malleable component. We investigated the relationship between dietary fibre intake, skeletal muscle mass and associated metabolic and functional parameters in adults aged 40 years and older. Methods: We analysed cross‐sectional data from the US National Health and Nutrition Examination Survey between 2011 and 2018 from adults aged 40 years and older. Covariate‐adjusted multiple linear regression analyses were used to evaluate the association between dietary fibre intake and BM components (BM, body mass index [BMI], total lean mass, appendicular lean mass, bone mineral content, total fat, trunk fat; n = 6454), glucose homeostasis (fasting glucose, fasting insulin, HOMA2‐IR; n = 5032) and skeletal muscle strength (combined grip strength; n = 5326). BM components and skeletal muscle strength were expressed relative to BM (per kg of BM). Results: Higher intakes of dietary fibre were significantly associated with increased relative total lean mass (β: 0.69 g/kg BM; 95% CI, 0.48–0.89 g/kg BM; P < 0.001), relative appendicular lean mass (β: 0.34 g/kg BM; 95% CI, 0.23–0.45 g/kg BM; P < 0.001), relative bone mineral content (β: 0.05 g/kg BM; 95% CI, 0.02–0.07 g/kg BM; P < 0.001) and relative combined grip strength (β: 0.002 kg/kg BM; 95% CI, 0.001–0.003 kg/kg BM; P < 0.001). Conversely, higher dietary fibre intakes were significantly associated with a lower BM (β: −0.20; 95% CI, −0.28 to −0.11 kg; P < 0.001), BMI (β: −0.08 kg/m 2 ; 95%CI, −0.10 to −0.05 kg/m 2 ), relative total fat (β: −0.68 g/kg BM; 95% CI, −0.89 to −0.47 g/kg BM; P < 0.001), relative trunk fat (β: −0.48 g/kg BM; 95%CI, −0.63 to −0.33 g/kg; P < 0.001), fasting glucose (β: −0.01 mmol/L; 95% CI, −0.02 to −0.00 mmol/L; P = 0.017), fasting insulin (β: −0.71 pmol/L; 95% CI, −1.01 to −0.41 pmol/L; P < 0.001) and HOMA2‐IR (β: −0.02 AU; 95% CI, −0.02 to −0.01 AU; P < 0.001). Conclusions: Higher dietary fibre intakes are associated with a lower BM and enhanced body composition, characterized by a reduction in fat mass and an increase in lean mass. Higher dietary fibre intakes were also associated with improvements in glucose homeostasis and skeletal muscle strength. Increasing dietary fibre intake may be a viable strategy to prevent age‐associated declines in skeletal muscle mass.